From Availability to Classroom Use: A Mixed-Methods Study of Learning Media Integration in Semarang Elementary Schools - Sundari, Riris Setyo; Ervina Eka Subekti; Fajar Cahyadi; Veryliana Purnamasari; Noor Dayana Abd Halim (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2026)
The integration of learning media is essential for supporting the implementation of the Kurikulum Merdeka, which emphasizes student-centered, technology-enhanced, and culturally responsive learning. However, disparities in the availability and utilization of learning media across elementary schools remain a challenge. This study aims to: (1) identify the availability and use of learning media in elementary schools in Semarang City; (2) analyze the gap between media availability, teacher competence, and classroom implementation; and (3) formulate policy recommendations to optimize learning media integration within the Kurikulum Merdeka and an ethnopedagogical framework. A mixed-methods explanatory sequential mixed-methods design approach was employed involving 42 teachers from 20 public and private elementary schools in Semarang City followed by interviews and observations in selected schools. Data were collected through questionnaires, interviews, and classroom observations. The findings indicate a clear gap between the availability of learning media and their effective classroom utilization. Although schools possess various conventional, digital, subject-specific, and ethnopedagogical learning media, their use remains dominated by textbooks and presentation-based resources. The implementation of interactive and technology-based media is constrained by disparities in teachers' technological and pedagogical competencies, uneven digital infrastructure, and limited institutional support. Ethnopedagogical media are available but have not yet been systematically integrated into everyday classroom instruction. The study recommends continuous teacher professional development, strengthened school support, and the systematic integration of digital and ethnopedagogical learning media to reduce the gap between media availability and classroom utilization